Mouse Strain Affects Behavioral and Neuroendocrine Stress Responses Following Administration of Probiotic Lactobacillus rhamnosus JB-1 or Traditional Antidepressant Fluoxetine - McVey Neufeld, Karen-Anne; Kay, Sebastian; Bienenstock, John (Frontiers in Neuroscience, 2018)
Currently, there is keen interest in the development of alternative therapies in the treatment of depression. Given the explosion of research on the microbiota-gut-brain axis, consideration has turned to the potential of probiotics to improve patient outcomes for those suffering from mood disorders. Here we examine the abilities of a known antidepressant, fluoxetine and the probiotic Lactobacillus rhamnosus JB-1TM, to attenuate responses to two established criteria for depressive-like behavior in animal models, the tail suspension test and the corticosterone response to an acute restraint stressor. We examine two strains of mice known to differ in the extent to which they express both anxiety-like behavior and measures of despair - BALB/c and Swiss Webster - with respectively high and normal behavioural phenotypes for each. While adult male BALB/c mice responded with increased antidepressive-like behavior to both fluoxetine and Lactobacillus rhamnosus JB-1 in both the tail suspension test and the corticosterone stress reponse, SW mice did not respond to either treatment as compared to controls. These findings highlight the importance of investigating putative antidepressants in mouse strains known to express face validity for some markers of depression. Clinical studies examining the activity of Lactobacillus rhamnosus JB-1 in patients suffering from mood disorders are warranted, as well as further pre-clinical work examining how interactions between host genotype and intestinal microbial alterations may impact behavioral responses. This study adds to the literature supporting the possibility that modifying the intestinal microbiota via probiotics represents a promising potential therapeutic breakthrough in the treatment of psychiatric disease.